Produção de massa de forragem e valor nutricional de híbridos de sorgo para produção de silagem - Moraes, Sheilla Davoglio de (2011)
The objective was to evaluate the production parameters and chemical composition of four sorghum hybrids (60015 XBS, XBS 60451, AG and Dow 2005 F305 E), and a hybrid corn (AS 32). The experimental design was a complete randomized block with three replications. For all the materials were evaluated total production of green mass (MV), dry matter (DM) and the stem, leaf, panicle, spike (maize). There were determined in forage the crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ether extract (EE), total carbohydrates (TC), non-fiber carbohydrates (NFC), mineral matter (MM) and organic matter (OM). There was no difference between hybrids for the production of DM, MV and leaf. Although the treatments did not differ significantly, the production of MV and DM was numerically greater for sorghum silage XBS 60015 with average values of 35,655 kg / ha and 12,767 kg / ha, respectively. All sorghum hybrids had higher average and the lowest was for corn production with an average of 26,398 kg / ha and 9,238 kg for MV / ha for DM. The production of stem was higher for maize AS 32 with 2205 t / ha and for sorghum XBS 60.451 with 2.042 t / ha. The increased production of sorghum panicle was for AG 2005 E with 5012 t / ha and for XBS 60451 with 3940 t / ha, whereas corn had the lowest average of 222 t /hectare/year. The chemical composition of sorghum and maize plants were not different among the hybrids, and for crude protein, sorghum AG 2005 had the highest average with 9.84% and corn 32 AS the smallest with 7.76%. For NDF, the lowest average was 55.57% for sorghum XBS 60015 while other hybrids had higher average with no significant differences. Sorghum AG 2005 had the highest average with 38.60% for FDA and maize AS 32 the lowest 28.87%. The other sorghum hybrids showed no differences between them. The major averages of EE have been presented by sorghum hybrids Dow 60015 and XBS F305 with 2.36% and 2.42% respectively. There was no difference among treatments for mean values of TC, NFC, MM and OM.